An investigation of a high-speed ground manoeuvre under optimal control. (September 2019) - Huang, Zexin; Best, Matthew; Knowles, James
This paper studies the behaviour of a nonlinear aircraft model under optimal control for aircraft ground manoeuvres, specifically for high-speed runway exits. The aircraft's behaviour on the ground is captured by a fully parameterised 6-DOF nonlinear model, which is developed in this work to model the effects of braking through a combined slip tyre model. A pre-defined cost function is minimised using a generalised optimal control algorithm to obtain an optimal control sequence for a particular manoeuvre-cost function combination. In this paper, three scenarios are investigated for a 45-degree high-speed runway exit: the first control sequence minimises the distance between the aircraft's centre of gravity and the runway centreline; the second maximises the distance travelled by the aircraft during the 20 s of simulation time; the third minimises tyre wear. For each scenario, the generalised optimal control algorithm provides the best possible control inputs. The dynamic response of the aircraft throughout the turn is shown to be dominated by its inertia, which suggests that future controllers will need to begin executing a turn far in advance of entering the corner. The results also provide a benchmark against which the effectiveness of future real-time controllers may be judged.